am+14+1=

Simple and best practice solution for am+14+1= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for am+14+1= equation:


Simplifying
am + 14 + 1 = 0

Reorder the terms:
14 + 1 + am = 0

Combine like terms: 14 + 1 = 15
15 + am = 0

Solving
15 + am = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + am = 0 + -15

Combine like terms: 15 + -15 = 0
0 + am = 0 + -15
am = 0 + -15

Combine like terms: 0 + -15 = -15
am = -15

Divide each side by 'm'.
a = -15m-1

Simplifying
a = -15m-1

See similar equations:

| 3x+5=4-(9x-8) | | z3-2=5 | | z/3-2=5 | | -2.1=n-7.5+0.8 | | 2x+37=90 | | 17+2x=31-2x | | 12(4+n)+5(-2n-9)=8 | | (5x^2+7x)(20x^2-11x-3)=0 | | 2a+1=148 | | 12(4+n)+5(-2-9)=8 | | 9xy-6yx+x-2y= | | 17x-13y=11 | | .5x+7=6 | | 180-3x=42x+20 | | 21x-3=-63 | | -2-5x=10x-8 | | 2x^2-24x-64=0 | | -159-(-172)= | | 3f-12=-f-15 | | y+3=10x | | 6x-4y-11y+7x+9= | | (2x^2-1)(4)-(x+1)(4)=0 | | 3a(4a-7)= | | 36-3y=-9 | | -(2x-1)-3x=-3(x+4) | | y-3=8x | | 2y^2=4y-1 | | -4+9x-4= | | 3x^2+7x+1=0 | | 3x+42-5x=2-6x+4 | | -4+9-4= | | y-8=3x |

Equations solver categories